POTENTIAL INHIBITORS AGAINST SARS-COV-2 BY TARGETING PROTEINS RESPONSIBLE FOR ENVELOPE FORMATION AND VIRION ASSEMBLY - KHATOON, ZEBA; CHAUDHARY, ANAMIKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Even though extreme research there is presently no efficient vaccine accessible against the new-found severe acute respiratory syndrome coronavirus-2 causing COVID-19 pandemic. The clinical administration of COVID-19 has been restricted to infection prevention along with control measures linked with supportive care. In the meantime, efforts to achieve a successful therapy to prevent virus replication, alleviate the symptoms, increase survivability as well as reduce mortality are ongoing. In this review, we found that a drug named Tipranavir (used in more than top 20 drugs in different countries against Covid-19) that can be docked against the QNH88662.1 envelope protein [Severe acute respiratory syndrome coronavirus 2] and at least cease the activity so that its action of spreading infection can be prevented. Pharmacokinetics and ADME studies show that drugs need some improvement. It is slightly heavier than Lipinski rule of five criteria. We propose improvement in future aspects.